Click Start 2: computer science for schools (cambridge) (Cambridge university press Karachi, 2014)
"Click Start" is an engaging educational series designed to introduce young learners to basic computer and ICT skills. It covers essential topics such as computer functions, software applications, and internet safety through interactive activities and colorful illustrations. The series aims to build digital literacy and confidence in using technology effectively.